2020
DOI: 10.1038/s41394-020-00363-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mid and low paraplegia on cardiorespiratory fitness and energy expenditure

Abstract: Study Design Observational, Cross-sectional. Objective Examine the influence of mid (MP) and low (LP) paraplegia on cardiorespiratory fitness (CRF), energy expenditure (EE), and physical activity levels (PAL), and compare these data to able-bodied (AB) individuals. Setting Academic medical center. Methods Persons with MP (n = 6, T6-T8, 83% male, age: 31 ± 11 y, BMI: 24 ± 7 kg/m 2 ) and LP (n = 5; T10-L1, 100% male, age: 39 ± 11 y, BMI: 26 ± 5 kg/m 2 ) and AB controls (n = 6; 67% male, age: 29 ± 12 y, BMI: 26 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…In the current study, measured BMR for the denervated group was 1597 ± 333 kcal/day. Farkas et al reported a mean measured BMR 1693 ± 329 kcal/day in five low paraplegic individuals using T9 as the demarcation point to account for individuals with a LMN (Farkas et al, 2020). In the present study, we showed that both SCI-specific equations developed by Chun et al and Nightingale & Gorgey (Models 1-3) significantly underpredicted BMR for the denervated male group.…”
Section: Denervated Males With Scisupporting
confidence: 50%
“…In the current study, measured BMR for the denervated group was 1597 ± 333 kcal/day. Farkas et al reported a mean measured BMR 1693 ± 329 kcal/day in five low paraplegic individuals using T9 as the demarcation point to account for individuals with a LMN (Farkas et al, 2020). In the present study, we showed that both SCI-specific equations developed by Chun et al and Nightingale & Gorgey (Models 1-3) significantly underpredicted BMR for the denervated male group.…”
Section: Denervated Males With Scisupporting
confidence: 50%
“…In addition, the age difference between the 2 groups may have affected the group comparison, as, in general, younger subjects are more likely to have higher cardiorespiratory fitness. However, it is generally difficult to establish groups of able-bodied and paraplegic subjects that are comparable in terms of cardiorespiratory fitness, as it has been well investigated ( 35 ) that paraplegic subjects have lower cardiorespiratory fitness in comparison with able-bodied subjects. In any case, only group comparisons may have been influenced by the age difference, the effects of propulsion mode are not affected.…”
Section: Discussionmentioning
confidence: 99%
“…After SCI, a MET is 2.7 mL/kg/min (0.189 L/min) [80], approximately 30% lower than persons without SCI. This reduced MET value, first reported by Collins et al [80] in SCI, is based on multiple factors, including decreased energy metabolism [6], limited oxygen utilization in sublesional active skeletal muscle [81], sympathetic nervous system dysfunction [82], an injury level-reduced cardiorespiratory response [83], and circulatory hypokinesis that hampers the hemodynamic response by restricting venous return and subsequently diminishing cardiac output [23]. Higher injury levels, often necessitating hand-securing devices for upper body PA modalities [84], exacerbate these factors [80].…”
Section: Physical Fitnessmentioning
confidence: 99%
“…For persons with and without SCI, authoritative guidelines established by expert panels endorse physical activity (PA) interventions as a practical approach to mitigating CMR [13–15,16 ▪▪ ,17 ▪▪ ,18–20]. However, compared to those without SCI, these PA guidelines may benefit from an additional evaluation of the diminished cardiorespiratory response to physical exertion in individuals with SCI [21–23]. Consequently, the initial prescription of PA may inadvertently lead to an insufficient PA volume by underestimating the duration and intensity required to address CMR effectively.…”
Section: Introductionmentioning
confidence: 99%